From impulse to loyalty: examining drivers of continuous purchase intention on the Tiktok live shopping platform - Lutfi Auliarahman (BISMA (Bisnis dan Manajemen), 2025)
TikTok live shopping, leveraging SOR Theory, enhances consumer impulsive buying and purchase intention through real-time influencer interactions. However, its potential remains underexplored in Indonesia, presenting a critical opportunity for brands to boost visibility and sales. This study introduces a novel exploration of the TikTok live shopping trend in Indonesia by employing Partial Least Square-Structural Equation Model (PLS-SEM) and Importance Performance Mapping Analysis (IPMA). This approach provides a unique perspective on consumer behaviour and engagement, offering valuable insights into the dynamics of this rapidly growing digital marketplace. This study uses a quantitative method by distributing questionnaires to 175 respondents who have made transactions through TikTok live shopping. This study found that enjoyment and social presence significantly influence online impulse buying in TikTok Live shopping, while attractiveness does not. Additionally, online impulse buying positively affects continuous purchase intention. This study reveals that while attractiveness is not a strong predictor of online impulsive buying. Enjoyment and social presence are crucial for enhancing consumer engagement. IPMA highlights the need for marketers to focus on these elements to drive impulse buying and sales. Brands should create engaging content and leverage promotions to maximise consumer interaction.